Analisa Energi pada Alat Desalinasi Air Laut Tenaga Surya Model Lereng Tunggal - Siregar, Munawar Alfansury; Damanik, Wawan Septiawan; Lubis, Sudirman (Jurnal Rekayasa Mesin, 2021)
The use of solar energy every day is increasing due to the greater human need for energy. the application of solar desalination equipment is classified as a renewable technology that is very profitable because the energy used is obtained for free and does not cause damage to the environment. This study examines the performance of the solar desalination device with a single slope model with a passive system. It is hoped that greater energy absorption is expected to accelerate the process of evaporation of seawater in the evaporator so as to produce lots of clean water. The desalination tool on the surface of the wall is insulated using aluminum foil with a thickness of 20 mm. The highest solar intensity was obtained on the fifth day of testing, namely 420.85 W/m2 with the radiation heat transfer coefficient of 18.44 W/m2 oC, and the lowest solar intensity on the second day, namely 96.89 W/m2 with the lowest total outside heat transfer coefficient of 25.57 W/m2 oC. The highest evaporative heat transfer coefficient is 10.54 W/m2 oC and the lowest is 4.42 W/m2 oC. the lowest energy absorbed by the evaporator on the second day was 1.37 kWh. And the highest efficiency on the fifth day reached 58.89% and the lowest energy efficiency on the second day, namely 34.05%.